Stiffness mapping of lower leg muscles during passive dorsiflexion. Issue 5 (2nd March 2017) - Le Sant, Guillaume; Nordez, Antoine; Andrade, Ricardo; Hug, François; Freitas, Sandro; Gross, Raphaël
Abstract: It is challenging to differentiate the mechanical properties of synergist muscles in vivo . Shear wave elastography can be used to quantify the shear modulus (i.e. an index of stiffness) of a specific muscle. This study assessed the passive behavior of lower leg muscles during passive dorsiflexion performed with the knee fully extended (experiment 1, n = 22) or with the knee flexed at 90° (experiment 2, n = 20). The shear modulus measurements were repeated twice during experiment 1 to assess the inter‐day reliability. During both experiments, the shear modulus of the following plantar flexors was randomly measured: gastrocnemii medialis (GM) and lateralis (GL), soleus (SOL), peroneus longus (PL), and the deep muscles flexor digitorum longus (FDL), flexor hallucis longus (FHL), tibialis posterior (TP). Two antagonist muscles tibialis anterior (TA), and extensor digitorum longus (EDL) were also recorded. Measurements were performed in different proximo‐distal regions for GM, GL and SOL. Inter‐day reliability was adequate for all muscles (coefficient of variation < 15%), except for TP. In experiment 1, GM exhibited the highest shear modulus at 80% of the maximal range of motion (128.5 ± 27.3 kPa) and was followed by GL (67.1 ± 24.1 kPa). In experiment 2, SOL exhibited the highest shear modulus (55.1 ± 18.0 kPa). The highest values of shear modulus were found for the distal locations of both the GM (80% of participants in experiment 1) and the SOL (100% of participants in experiment 2). For both experiments, deep muscles and PL exhibited low levels of stiffness during the stretch in young asymptomatic adults, which was unknown until now. These results provide a deeper understanding of passive mechanical properties and the distribution of stiffness between and within the plantar flexor muscles during stretching between them and thus could be relevant to study the effects of aging, disease progression, and rehabilitation on stiffness.